Solid state photoelectrochemical cells utilising graphite thin films counter electrode - Rahman M.Y.A.; Salleh M.M.; Talib I.A.; Yahaya M. (2023)
This paper reports the use of graphite thin films as a counter electrode of a solid state photoelectrochemical cells of ITO/TiO2/PVC-LiClO 4graphite. The photoelectrochemical cells material was a screen-printed layer of titanium dioxide onto an ITO-covered glass substrate which was used as a working electrode of the device. The solid electrolyte used was PVC-LiClO4 that was prepared by solution casting technique. The graphite films which serve as a counter electrode were prepared onto glass substrate by electron beam evaporation technique at substrate temperatures variation of 25, 50, 100, 150 and 200C. The dependence of sheet resistance and surface morphology of the graphite films on substrate temperature were studied. The films deposited at 25C shows the smoothest surface morphology and the smallest grain size. Bigger grain size, rougher surface morphology of graphite film counter electrode. The current-voltage characteristics of four devices utilising the graphite counter electrode with different substrate temperature in dark as well as under illumination of 100 mWcm-2light from a tungsten halogen lamp were recorded at room temperature and at 50C, respectively. It was found that the photovoltaic parameters of the device such as short-circuit current density, Jsc and open-circuit voltage, Voc increases with the decreasing average grain size of the graphite counter electrode. The device whose graphite film counter electrode was deposited onto the glass substrate at 25C gave the highest Jsc of 0.32 ?A/cm2 and Voc of 117 mV, respectively.